PENGARUH PENDAPATAN ORANG TUA TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA KELAS X DI SMKN 2 JIWAN KABUPATEN MADIUN TAHUN 2011/2012 - Onnes Andong Kartiko (Universitas PGRI Madiun, 2013)
Family represent first social institute which recognized by child and in this family can be inculcated attitudes able to influence growth of child hereinafter. Family hold responsible to provide fund for the requirement of to education of child. Family ( old fellow) which situation of high economic social will not finding difficulties many in fulfilling requirement of child school, differing from old fellow is situation of his eco- nomic social lower. Target of this research is 1. To know the condition of earnings of class student old fellow of X SMKN 2 Jiwan Sub-Province of Madiun in the year lesson 2011 /20122. To know achievement learn student of X SMKN 2 Jiwan Sub-Province of Madiun in the year lesson 2011 /2012 3. To know influence of earnings of old fellow to achievement learn class of X SMKN 2 Jiwan Sub-Province of Madiun School year 2011 / 2012. Research method used in this research is method of diskriptif with its analysis desain wear regresi. Procedure data collecting bibliography study and research of field. Study bibliography of writer do by reading various erudite compositions or book which concerning theory framework is relefan with problem of is studied. Research of field medium to obtain.get primary data obtained to through documents which have made available, on the other hand data of sekunder by Method enquette and observation In this research, enquette used to know the condition of economic social of old fellow. Technics of data analysis used by analysis of statistic with linear regresi modestly, and to be tested its hypothesis utilized test of t or difference of mean. From result of research by using Equation of expressed doubled linear regression: Equation of the doubled linear regres- sion have positive value at konstanta that is 54.26 expressing that if earnings of valuable old fellow zero hence achievement learn student will be valuable 54.26. 54.26, coeffi- cient of Regresi variable of X is positive equal to 0.36, please express that each;every earnings of old fellow go up equal to one set of hence will cause improvement or increase of achievement learn equal to 0,36 one set of. Its meaning of the influence [is] influence which are positive. Level of value ofThitung equal to 29,02 signifikansi 0.05 with counter df equal to 1 and denominator df equal to 30 is so that obtained by value of t-tabel equal to 1.699. Pursuant to result of the comparison seen that thitung>ttabel (29.02>1.699). Thereby [job/activity] hypothesis (Ha) expressing that there is positive influence [among/ between] earnings of old fellow old fellow to achievement learn student of SMK NEGERI 2 JIWAN